Manajemen Laba: Strategi Bisnis, Investment Opportunity Set, Managerial Entrenchment dan Ukuran Perusahaan - Masri, Suci Indiarti; Khairunnisa (Politeknik Ganesha Medan, 2024)
One of the most important information is profit information that investors can consider when making investment decisions. Company managers use this information to commit financial statement fraud at profit levels to increase company profits, one of which is earnings management practices. The purpose of this research is to examine and determine the effect of business strategy, investment opportunity set, managerial entrenchment and firm size on earnings management. The population used in this study are transportation and logistics companies listed on the Indonesia Stock Exchange (IDX) in the 2017-2021 period. Sampling by method purpose sampling and according to the criteria obtained 70 sample units from 14 companies within 5 years. Data analysis using panel data regression. The results of the study show that business strategy, investment opportunity set, managerial entrenchment and firm size simultan eously influence earnings management. Partially, business strategy, managerial entrenchment and the size of the company has no effect on Earnings Management. Whereas, investment opportunity set has a positive influence on Earnings Management.